Phacoemulsification of the crystalline lens and implantation of an intraocular lens for the correction of moderate and high myopia: Four-year follow-up (2003)
Purpose: To assess the safety of lens extraction and intraocular lens (IOL) implantation in patients with high myopia treated for initial lens opacity and/or refractive indications. Setting: Instituto de Microcirugfa Ocular de Barcelona, Barcelona, Spain. Methods: This retrospective nonrandomized case series study comprised 44 eyes of 30 consecutive myopic patients who had surgery because of initial lens opacity and/or refractive indications during a 2-year period. In each case, phacoemulsification was performed using an ultrasonic technique and an IOL was implanted in the capsular bag. The patients were seen preoperatively to evaluate retinal pathology. They also had a complete ophthalmologic evaluation that included detailed indirect ophthalmoscopy. All patients were followed at regular intervals. The main outcome measures were preoperative and postoperative-spherical equivalent (SE), the incidence of posterior capsule opacification (PCO) and the need for capsulotomy, and the incidence of retinal complications. Results: In all eyes, the surgery was uneventful. The mean patient age at surgery was 42.83 years; the mean preoperative SE was -15.77 diopters (D) and the mean postoperative SE, -1.05 D. No eye required preoperative peripheral retinal photocoagulation. Twenty-five eyes (56.8%) had PCO and had a neodymium:YAG laser capsulotomy. One eye had a retinal tear 14 months after surgery and was treated with focal photocoagulation. The mean endothelial cell loss was 2.1% during the first postoperative year. Two eyes had an immediate postoperative intraocular pressure (IOP)rise, 1 with an inflammatory membrane and the other with corneal edema; both resolved with topical treatment. One eye with elevated IOP and a bad response to medical treatment had argon laser trabeculoplasty. No eye had a retinal detachment during the follow-up. Conclusion: With a thorough preoperative ophthalmologic evaluation and uneventful surgery, patients who have phacoemulsification and IOL implantation for the correction of myopia have a satisfactory chance of obtaining good visual results with few complications. ©2003 ASCRS and ESCRS.